Effect of pre-evisceration, skin-on carcass decontamination sanitation strategies for reducing bacterial contamination of cattle during skinning - Calicioglu, Mehmet; Buege, Dennis R.; Luchansky, John B. (Tubitak Scientific & Technological Research Council Turkey, 2010)
The effectiveness of pre-evisceration, skin-on carcass sanitation on reducing bacterial contamination of beef carcasses was tested using 3 cattle per treatment and 3 cattle as controls at each of 3 abattoirs in southern Wisconsin. The sanitation procedure included stunning, bleeding, tying off the esophagus, sealing the anus, and then sanitizing the hide with: i) 20% trisodium phosphate, ii) 200 ppm iodophor, iii) 75% ethanol, or iv) hot water (ca. 80 degrees C). Two sets of combined sponge samples (3 x 100 cm(2)) were taken from the hide before and after the sanitation step, as well as from the carcass after the final wash. Our results revealed that average reductions in numbers of total aerobic bacteria on the hide ranged from 0.06 to 3.58 log(10) cfu per cm(2) depending on the sanitation method. However, regardless of the various sanitation methods tested, no significant differences were found between test and control groups in the level of total aerobic bacterial contamination on the carcasses after the final wash.
Yüzüm öncesi-derili karkas dekontaminasyon sanitasyon stratejilerinin si?ir karkaslarinda derinin yüzülmesi esnasinda oluşan bakteriyel kontaminasyonun azaltilmasina etkisi
Keywords: Pre-evisceration; beef carcass decontamination; sanitation; adhesive; trisodium phosphate (TSP); iodophor; ethanol; hot water